Contracting in a market with differential information - Rocha, M.; Greve, T. (Journal of Industry, Competition and Trade, 2021)
Today’s technology allows firms to collect, store and use different types of data. This has prompted a wide discussion on the effects of access to data on competition and consumer welfare. This discussion has also been present in the energy sector in which advanced technology has allowed for the collection of detailed energy consumption data. Prompted by this discussion on the energy sector, this paper studies an industry where two firms have access to the same technology and compete in prices, but one of them has access to better information about customers. The better informed firm obtains a customer contact advantage, whereas the uninformed firm can still offer a menu of prices without being able to pre-identify the customers. We show that the better informed firm is able to exclude the uninformed firm from the market. This result provides policy insights on the usefulness of considering data access models that can ensure non-discriminatory behaviour.